(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Many traditional medicines are obtained mainly from medicinal plants, minerals and organic matter. During the past many years, there has been increasing interest among the uses of various medicinal plants from the traditional system of medicine for the treatment of different ailments. Coccinia indica is one such important medicinal plant which belongs to the family Cucurbitaceae. It is extensively used as a vegetable and grown widely throughout the Indian Subcontinent. It is commonly called ’Kundra’ in India. Traditionally different parts of this plant namely the roots, leaves and fruits are utilized in folklore medicine for several purposes, especially for hypoglycemia and skin diseases. There are many patented formulations derived from Coccinia indica plant. This plant is a primary source from where we get different phytochemicals which are utilized as the main constituent in numerous formulations endorsed for several ailments. Coccinia indica plant possesses many therapeutic activities like antidiabetic, hypolipidemic, hepatoprotective, larvicidal, anti-inflammatory, analgesic and antipyretic activities. The present review provides adequate information, photochemistry and various medicinal uses of Coccinia indica plant.